Credibility, transparency, and sustainability in fashion: a game-theoretic perspective. (19th April 2023) - Nandkeolyar, Olivia; Chen, Frederick
Abstract: We present a game-theoretic model of a firm's production decision to analyze the conditions under which the firm would engage in sustainable practices when there exists a certification agency that can audit the firm. Our results show that when the certification agency is firm-owned or when it is an independent, profit-maximizing entity, then there is no equilibrium in which the firm chooses to produce in a sustainable manner. We also present real-world examples from the apparel and footwear industry, as well as the mining industry, that are consistent with our theoretical results. We consider what would happen if the certification agency is government-operated or a non-profit organization with a mandate to monitor the firm's production process. We show that – combined with tax incentives or subsidies for the firm if necessary, and greater specificity regarding what is sustainable – there exists an equilibrium in which the firm would choose to engage in sustainable production in this case. We analyze extensions of the model to examine conditions under which the phenomenon of greenwashing can arise as an equilibrium outcome. We also propose a "bounty system" that the government can implement to incentivize monitoring of firms' production processes, and we show how such a policy can induce more sustainable production practices by the firm.